2012
DOI: 10.1039/c2cp42037f
|View full text |Cite
|
Sign up to set email alerts
|

Optoelectronic properties of (ZnO)60 isomers

Abstract: We studied the optoelectronic properties of six possible structures of the (ZnO)(60) cluster using density functional theory (DFT). Vertical ionization energies and electron affinities are calculated through total energy differences, while the optical absorption spectra are obtained by using hybrid time-dependent DFT. The (ZnO)(60) cluster has been proven to be particularly stable and it is of potential interest for future applications in nanoelectronics, but its ground-state configuration has been unknown to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…A core-cage structure for (ZnO) 34 has been proposed as the most stable in [ 10 , 11 ], while [ 12 ] have predicted the hollow cage structures formed by (ZnO) 2 squares and (ZnO) 3 hexagons. In the case of (ZnO) 60 , the studies [ 13 , 14 ] revealed an energetically preferred sodalite motif, while nested cage configuration was predicted to be the most stable in [ 10 , 11 ]. Such differences indicate that there is a strong dependence of the calculated binding energy on the details of the computational framework adopted.…”
Section: Introductionmentioning
confidence: 99%
“…A core-cage structure for (ZnO) 34 has been proposed as the most stable in [ 10 , 11 ], while [ 12 ] have predicted the hollow cage structures formed by (ZnO) 2 squares and (ZnO) 3 hexagons. In the case of (ZnO) 60 , the studies [ 13 , 14 ] revealed an energetically preferred sodalite motif, while nested cage configuration was predicted to be the most stable in [ 10 , 11 ]. Such differences indicate that there is a strong dependence of the calculated binding energy on the details of the computational framework adopted.…”
Section: Introductionmentioning
confidence: 99%
“…28 From these results, the relative stability of the isomers considered strongly depends on the computational scheme adopted. 31 Likewise, two isomers have been proposed to explain the unmatched stability of the (CdSe) 33 stoichiometry, namely a core@cage cluster ((CdSe) 5 @(CdSe) 28 ) 19 and a wurtzite-like arrangement. 32 However, the simple analysis of the energy differences can not be conclusive to determine the lowest-lying isomer.…”
Section: Introductionmentioning
confidence: 99%
“…30,36 Motivated by the recent experimental work by Wang et al, 38 where the magic (CdSe) 13 has been isolated for the first time, we further progress in the characterization of the putative isomers of (CdSe) 13 and of their amine-capped counterparts. As already made for (ZnO) 60 , 31 energy calculations are combined with TDDFT spectra in order to identify the isomer found in the experiment. Our results are in excellent agreement with the experimental measurements recorded in toluene.…”
Section: Introductionmentioning
confidence: 99%
“…ZnO nanoclusters have been studied extensively 2,47,[57][58][59][60][61][62][63][64][65][66][67][68][69][70][71] and most of the studies report that the larger LM structures typically resemble bubbles and nanotubes. As we have access to the data published by Al-Sunaidi et al, 47 and as it is the first and only systematic study that also includes the low energy metastable (ZnO) n configurations up to n = 32, we have used these results as our benchmark.…”
Section: (Zno) N N = 1-32mentioning
confidence: 99%